Conceptual design of a third generation aerobatic aircraft. (June 2023) - Goraj, Zdobyslaw; Frydrychewicz, Andrzej; Danilecki, Stanislaw; Olejnik, Aleksander; Kiszkowiak, Łukasz
This paper presents the development of an aerobatic aircraft including the influence of platform configuration on performance, elegance and safety of aerobatic manoeuvres. Several aircraft of different wing loadings were compared and the reduction of wing loading on manoeuvring slowdown was studied. Advantages of the biplane configuration influence on the desired properties of aerobatic aircraft were discussed in detail. Results of numerical simulations obtained for HARNAS-3 aircraft were compared with corresponding results received for EXTRA 300 aircraft. Some original design solutions for HARNAS-3, enabling easier control of this aircraft during the manoeuvring phase, were presented. Numerical simulations, wind tunnel tests and free flight experimental results for scaled-down HARNAS-3 models were presented, compared and discussed.